2014
DOI: 10.5539/jas.v6n3p23
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Application Timing: Influence in Wheat Grain and Flour Selenium Accumulation Under Mediterranean Conditions

Abstract: Millions of people have an inadequate supply of selenium (Se) and Se-biofortified crops could prevent such deficiency. In order to establish an effective Se biofortification program under Mediterranean conditions on wheat, the objective of the present study was to evaluate the effect of the Se application timing on the Se accumulation in the grain, yield and protein content. In a field experiment, ten g ha -1 of sodium selenate were foliar-applied at four different growth stages: at 1 st node detectable (GS-31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
(29 reference statements)
3
8
1
Order By: Relevance
“…A significant and positive correlation between grain Se concentration and the amount of precipitation during the growing season have been already indicated (Johnson, 1991). This result was in line with the general recommendation (application at GS-45 stage, at boots just swollen) given for humid regions (Rodrigo et al, 2014). Other authors have reported a better Se accumulation when Se was applied at flowering stage (Curtin et al, 2006) or even at grain filling (Chu et al, 2013) in humid regions or in irrigated crops.…”
Section: Higher Translocation Of Se From Roots To Shoots and From Shosupporting
confidence: 84%
“…A significant and positive correlation between grain Se concentration and the amount of precipitation during the growing season have been already indicated (Johnson, 1991). This result was in line with the general recommendation (application at GS-45 stage, at boots just swollen) given for humid regions (Rodrigo et al, 2014). Other authors have reported a better Se accumulation when Se was applied at flowering stage (Curtin et al, 2006) or even at grain filling (Chu et al, 2013) in humid regions or in irrigated crops.…”
Section: Higher Translocation Of Se From Roots To Shoots and From Shosupporting
confidence: 84%
“…Selenium concentration in many soils all over the world, although very variable, can be considered low, ranging between 10 and 2000 μg kg −1 , with an average value of 400 μg kg −1 (Arthur 2003). In the southwestern Iberian Peninsula, several studies have established values of Se in soils of about 140 μg total Se kg −1 and 12 μg extractable Se kg −1 (Poblaciones et al 2014;Rodrigo et al 2014). These levels can be considered deficient to marginal according to the classification given by Dinh et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that foliar Se application is more efficient than soil amendment due to lower fertilizer doses and leaching losses from and Se fixation in the soil ( Tveitnes et al., ). Selenate is more available for immediate uptake than selenite ( Stroud et al., ; Poblaciones et al., ; ; ; Rodrigo et al., ); foliar Se application after flowering ( i.e ., in the reproductive stage) is the most efficient way to increase grain Se concentration ( Chu et al., ; Rodrigo et al., ).…”
Section: Introductionmentioning
confidence: 99%